2010
DOI: 10.1159/000313011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Context of Scent-Marking in Callithrix penicillata

Abstract: Most mammals use olfactory signals for communicating identity, reproductive status and group-related dynamics. Callitrichids produce secretions as olfactory signals, the functional context of which is poorly known, especially in the wild. We analysed the functional significance of scent-marking in a free-ranging group of Callithrix penicillata in central Brazil. We recorded all occurrences of scent-marking according to context and conducted 10-min focal observations of adults and ‘scan sampling’ of the focal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, to counteract these external variations, animals could alter their behaviour to ensure effective information transfer. For example, the scent marking frequency of black-tufted marmosets (Callithrix penicillata) was positively correlated with humidity (Oliveira and Macedo 2010), while aardwolves (Proteles cristata) increased scent marking during the summer wet season (Marneweck et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, to counteract these external variations, animals could alter their behaviour to ensure effective information transfer. For example, the scent marking frequency of black-tufted marmosets (Callithrix penicillata) was positively correlated with humidity (Oliveira and Macedo 2010), while aardwolves (Proteles cristata) increased scent marking during the summer wet season (Marneweck et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been reported to be either territorial or serving to label a food source (Lazaro-Perea et al, 1999; Oliveira & Macedo, 2010). ‘Phee calling’ (loud single- or multisyllable whistle).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, one study [80] found that there were significant differences in scent-marking behaviour between the sexes in the moustached tamarin (Saguinus mystax) with females marking more frequently. Despite finding no difference in the frequency of marking between the sexes in black-tufted marmosets (Callithrix penicillate), there were significant differences in scent-mark deposition between males and females, suggesting different functions for marking in the two sexes [77].…”
Section: Olfactory Communication In Primatesmentioning
confidence: 79%
“…Both strepsirrhine species and South American monkeys rely on olfactory senses for different functions, such as foraging and communication of a variety of messages [68]. Most South American monkeys have specialized sternal or anogenital scent glands and produce odours via secretions from these glands [68,77]. For example, one study [78] was able to identify 162 chemical compounds from the scent marks of female common marmosets (Callithrix jacchus) and found that the relative abundance of compounds differed between individuals, indicating a role in identification.…”
Section: Olfactory Communication In Primatesmentioning
confidence: 99%